Opto-electrical properties of indium gallium arsenic phosphide quaternary epilayers and multiple quantum wells lattice matched to indium phosphide. - Demerdjiev, Penka. (University of Ottawa (Canada), 1995)
$In\sb{1-{\rm x}}Ga\sb{\rm x}As\sb{\rm y}P\sb{1-{\rm y}}$ epilayers lattice matched to InP and $In\sb{1-{\rm x}}Ga\sb{\rm x}As\sb{\rm y}P\sb{1-{\rm y}}/InP$ Multiple Quantum Wells (MQWs) grown by Chemical-Beam Epitaxy (CBE) are being studied systematically using the Photovoltaic (PV) effect. At first, the Schottky barriers on the interfaces (metal-semiconductor, metal-insulator-semiconductor) are determined as an important factor for the electrical and optical properties of the samples. Samples with identical Schottky contact deposition but with an insulating layer on the front surface, have shown much smaller leakage current and yield enhanced barrier heights. The photovoltaic signal in the temperature interval 4-300K has maximum amplitude at about 150-180K for the MQW samples and at about 190K for the epilayer. An applied electric field changes the integrated intensity and spectrally shifts the allowed and forbidden transitions observed in bias dependent PV spectra of various InGaAsP/InP MQWs. The combined effect of two external factors, the thermal ionization and the electric field on the shape and magnitude of the 11H exciton peak, are discussed in terms of exciton binding energy and field ionization. The optically induced changes and energy shifting of the 11H/ exciton peak are observed, when excitation dependent double beam experiments are conducted on the $In\sb{0.72}Ga\sb{0.28}As\sb{0.68}P\sb{0.32}/InP$ MQWs. The photomodulation of the internal fields through carrier transport results in observing effective nonlinearities at milliwatt power levels. The experimentally measured transition energies for the MQWs show good agreement with the envelope wave function calculations. The observed Schottky barrier heights and band gap energies are consistent with the interpolation scheme estimations. (Abstract shortened by UMI.)
Keywords: Physics, Condensed Matter.